The effects of home visiting on mother-child interactions: Evidence from a randomized trial using dynamic micro-level data. (May 2021) - Conti, Gabriella; Poupakis, Stavros; Sandner, Malte; Kliem, Sören
Abstract: Background: Home visiting programs constitute an important policy to support vulnerable families with young children. One of their principal aims is to improve infant-parent relationships, so a key measure of their effectiveness is based on observational measures of parent-children interactions. In the present study we provide novel evidence on the effectiveness of home visiting programs in improving mother-child interactions within a randomized controlled trial (RCT) of the Pro Kind program. A major goal of the Pro Kind program is to promote child development by strengthening the intuitive parenting skills of mothers. On this basis, the following research question is addressed in this paper: What is the impact of the Pro Kind home visitation program on the quality of mother-child interaction? Methods: A randomly chosen subsample of the original sample was selected to participate on video recordings. This subsample of 109 mother-child dyads was videotaped during a 3-min typical play situation at the participants' homes when the child was aged 25 months. We use a novel micro-coding system which allows us to examine how the intervention affected the dynamic feedback responses of both mothers and children in three key measures of behavior: orientation, positive contingency, and negative/lack of contingency. The analysis was conducted using a set of static probit models and dynamic cross-lagged panel probit models for each measure. Results: The intervention significantly improved the interactions between girls and their mothers, by increasing the prevalence of orientation and positive contingency (and reducing that of negative/lack of contingency). This was achieved by increasing both the persistence of positive behaviors and also the probability of switching from negative to positive behaviors in the treatment group. Mixed impacts were detected for boys. Conclusions: Overall, it can be said that the Pro Kind program has a positive impact on the quality of mother-daughter interaction. However, our findings might also influence the design and delivery of home visiting programs, to the extent that they suggest that more attention has to be devoted to the interactions between boys and their mothers. Furthermore, the results show the importance of careful dynamic modelling of interactions data from videotaped observations to have a more complete understanding of the effectiveness of home visiting programs.